Repatriation or Redefection? Cold War Refugees as Contested Assets, 1955–1956 - Mazurkiewicz, Anna (Two Homelands, 2022)
The article examines the response of a united representation of Cold War era exiles (Assembly of Captive European Nations, ACEN) to the Moscow-inspired repatriation campaign of 1955. The article’s focus rests on the US-sponsored exile political activities carried under the aegis of the Free Europe Committee. The year 1955 serves as a particularly interesting moment when both key adversaries in the Cold War were engaged in programs using migration as a tool to advance their political goals. The issue of political exiles’ agency is signaled based on the Polish case in the context of American redefection programs and Washington’s response to the Soviet Bloc campaign to demoralize anti-communist escapees and induce their return.